If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-l6=(-2)l+9
We move all terms to the left:
-l6-((-2)l+9)=0
We add all the numbers together, and all the variables
-1l^6-((-2)l+9)=0
We calculate terms in parentheses: -((-2)l+9), so:We do not support elpression: l^6
(-2)l+9
We multiply parentheses
-2l+9
Back to the equation:
-(-2l+9)
| 3x^2+5x+20=16+x+x^2 | | 6b-2b-5b=1+14-7 | | 18d-12d+3D=10 | | x/8+4=-12 | | -7y-13=5y+11 | | –3=4-y/3 | | y-16+2y+118=180 | | 16x^2-4x=6 | | 6j-5j=10 | | 9c-8c=15 | | y-17+2y+118=180 | | 7/5x-9.42-2/5x-1.58=0 | | -x/12+25=29 | | -2x^2-4x-1=2x+4 | | -9+n=11/ | | -5(3c-9)=35-8c | | 23=1.5x+20 | | 3x+50+5x+12=180 | | -17+2(6x-1)+5=0 | | 3*2x-5=4x+7 | | 3(x+4)-4=2(2x+5)-x | | 34+34+4y=180 | | 16q-15q=17 | | -53=8x+4x-7 | | -9f-2-8f=-19 | | –29=q−68 | | 5x+8=32+3xx= | | 5x+8=32+3x | | 3(y-6)+8=4(y+7) | | 3v+14=5v+2 | | 2b−–3=7 | | 6x-4=12x+15 |